2019
DOI: 10.1111/ina.12537
|View full text |Cite
|
Sign up to set email alerts
|

Personal exposure to PM 2.5 in Chinese rural households in the Yangtze River Delta

Abstract: High levels of PM2.5 exposure and associated health risks are of great concern in rural China. For this study, we used portable PM2.5 monitors for monitoring concentrations online, recorded personal time‐activity patterns, and analyzed the contribution from different microenvironments in rural areas of the Yangtze River Delta, China. The daily exposure levels of rural participants were 66 μg/m3 (SD 40) in winter and 65 μg/m3 (SD 16) in summer. Indoor exposure levels were usually higher than outdoor levels. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…A study conducted in Yunnan, China, contrasting personal exposure to PM 2.5 in non-pregnant women primarily using improved fuels (LPG and electricity) with non-pregnant women primarily using biomass fuels reported a difference of personal exposure of 24% (91 µg/m 3 vs. 119 µg/m 3 ) [21]. Another study in the Yangtze River Delta in China reported a personal exposure to PM 2.5 of 58 µg/m 3 of PM 2.5 in people using LPG and 77 µg/m 3 in people using biomass, a 24% difference [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in Yunnan, China, contrasting personal exposure to PM 2.5 in non-pregnant women primarily using improved fuels (LPG and electricity) with non-pregnant women primarily using biomass fuels reported a difference of personal exposure of 24% (91 µg/m 3 vs. 119 µg/m 3 ) [21]. Another study in the Yangtze River Delta in China reported a personal exposure to PM 2.5 of 58 µg/m 3 of PM 2.5 in people using LPG and 77 µg/m 3 in people using biomass, a 24% difference [20].…”
Section: Discussionmentioning
confidence: 99%
“…An intervention study aiming at estimating effectiveness conducted in Guatemala showed a 45% reduction in 24-h PM 3.5 concentrations for LPG compared to the open fire [19]. Moreover, observational studies had reported percent differences in personal HAP exposure associated with LPG use ranging from 33% to 25% [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…That shows the dominating role of the weather pattern, in particular wind speed and atmospheric stability, in controlling the concentrations of PM 10 in ambient air in Kraków. In the case of PM 2.5 , the daily WHO air quality limit guideline of 25 μg m −3 can be considered as an allowed threshold (Hu et al 2019), because in Polish legislation there is no mean daily PM 2.5 concentration limit accepted. For outdoor concentrations, the allowed mean daily value of 25 μg m −3 was exceeded only on 2 days during good weather conditions, while during poor conditions the limit was largely exceeded on all days.…”
Section: Resultsmentioning
confidence: 99%
“…From 98 days with PM measurements, 23 days were chosen which fulfilled the criteria, 11 days with very good weather conditions (i.e., with high wind speed) and 12 days with very poor conditions (i.e., low wind speed). The number of days analyzed seems to be sufficient for drawing the conclusions, as many studies on indoor air pollution are realized with short-term measurements, e.g., Pekey et al (2010) used measurements from 30 days selected from a 2-month measurement campaign, MacNeill et al (2014) based their study on measurements from seven consecutive days in both summer and winter, Hu et al (2019) conducted the measurements in three 2-week periods, Cao et al (2005) measured indoor and outdoor concentrations in three localities and each of them for 3 days, and Blondeau et al (2005) carried out the measurements for two 2-week periods in each of 8 localities, one during winter and the other during spring or summer. Additionally, the chosen days present only extreme, border conditions, i.e., either very good or very poor weather conditions, so as to show the differences in the impact on indoor concentrations clearly.…”
Section: Methodsmentioning
confidence: 99%
“…Personal monitoring of airborne PM is intended to account for variability in PM exposures that are attributable to variability in individual behaviors and living conditions . Technological developments in the size, weight, noise, and cost of personal air samplers contributed to an increase in direct sampling of personal PM 2.5 exposures in settings with HAP over the last decade. These studies showed high within-subject variability in exposures and relatively small differences between clean fuel and solid fuel users, which could be driven by diverse factors including outdoor air pollution, unidentified sources, variability in emissions based on fuel characteristics or stove performance, and solid fuel use in nearby homes. , Chemical analysis of PM 2.5 samples could provide information about the relative impacts of these factors on exposure reductions or lack thereof; however, only a small handful of these studies included chemical analysis , , and even fewer measured source-specific tracers (e.g., levoglucosan). ,,, …”
Section: Introductionmentioning
confidence: 99%